Revisiting the “Surveillant Assemblage” - Newell, Bryce Clayton; Hughes, Lizzie (Surveillance & Society)

(untitled) (Surveillance Studies Network, 2025)
The “surveillant assemblage” and its attendant notion of the “data double” have held a central place within surveillance theory for nearly a quarter of a century. Haggerty and Ericson proposed the concept as a way to push back against prevailing, and limited, surveillance theory rooted in Foucauldian panopticism and Orwellian notions of “big brother.” Yet, in an informational and technological landscape that has changed significantly since 2000, and continues to change rapidly, it seems vital to ask whether a concept like the surveillant assemblage continues to have meaningful application to surveillance today. In this Dialogue, we bring together surveillance scholars from across the humanities and social sciences to look at how the “surveillant assemblage” has contributed to surveillance scholarship and informed our thinking about surveillance in society. The Dialogue includes six interventions from scholars who apply, extend, refashion, and critique the surveillant assemblage, as well as a closing response from Kevin Haggerty—the first time he has chosen to directly revisit the idea of the surveillant assemblage. In his response, Haggerty outlines a proposal for shifting our attention to understanding surveillance as a process of “surveillantization.”